P16 Prospective risk of osteoporotic fracture in patients with advanced COPD. (12th November 2015) - Gupta, A; Greening, NJ; Evans, RA; Toms, N; Samuels, A; Steiner, MC
Abstract : Introduction: COPD is associated with an increased prevalence of osteoporosis with shared risk factors including smoking, low BMI and reduced mobility. However, the risk of future fractures is not routinely considered in the management of COPD. We aimed to quantify future fracture likelihood and identify factors associated with an increased probability of osteoporotic fractures in patients with advanced COPD. Methods: Patients with advanced COPD were prospectively recruited and underwent a 'comprehensive respiratory assessment' as previously described. 1 The 10 year probability of developing either a major osteoporotic fracture or hip fracture was calculated using the fracture risk assessment tool (FRAX®) 2 using routinely collected data including age, gender, weight, height, smoking history, alcohol use, presence of inflammatory arthritis, corticosteroid use, but with the omission of family history and prior history of fractures. High risk was considered to be a ≥20% probability of a major osteoporotic fracture and ≥5% probability of a hip fracture. Results: 181 patients were included: mean (SD) age of 65 (9) years, MRC score 4 (IQR 0), BMI 25.4 (6.9) kg/m 2, 42% female and 25% current smokers. The mean (SD) 10-year probability for a major osteoporotic fracture was 9.1 (5.1)% and for a hip fracture was 3.5 (3.6)%. 43 (24)% of patients were considered to be high probability of a future fracture. 25 (14%) patients were prescribed a bisphosphonate and 17 (9%) maintenance daily oral prednisolone. Only 4 (24%) patients on oral steroids had a high probability for a future osteoporotic fracture. The cohort was divided into quartiles based on FRAX® score for future major osteoporotic fractures. There were significant differences between groups in exercise capacity, quadriceps strength, exacerbations, body composition and a trend to home oxygen use (Table 1 ). Conclusion: A quarter of patients with advanced COPD had a high probability of a future major osteoporotic fracture despite our calculations being an underestimate. An increased likelihood of fracture was associated with a number of potentially modifiable measures including exacerbation frequency, reduced physical performance and reduced skeletal muscle bulk. References: 1 Steiner MC. Thorax 2015;70 (8):805–808 2 Kanis JA. Lancet 2002;359 :1929–36